Reliability and validity of adapted cross-cultural counselling inventory-revised on the sample of undergraduate counsellor trainees - Maizatul Mardiana Harun; Wan Marzuki Wan Jaafar; Asmah Ismail; Sidek Mohd Noah (International Journal of Evaluation and Research in Education (IJERE), 2022)
The cross-cultural counseling inventory-revised (CCCI-R) is one of the limited instruments available to measure the observed multicultural counselling competence. Most studies utilized self-report multicultural counselling competence instruments. Therefore, for the benefit of counsellor educators and multicultural training in Malaysia, this study investigated the factor structure, reliability, and validity of the adapted CCCI-R in the local context. There were 38 supervisors who completed 205 the adapted CCCI-R for their respective counsellor trainees. As the result, internal consistency was found to be=.947, while construct reliability was found to be .968. The confirmatory factor analysis (CFA) yielded a convergent validity value of .909. The adapted CCCI-R factor structure, reliability, and validity were all verified in this study. Counsellor educators were able to successfully employ the CCCI-R across gender and ethnicity when rating counsellor trainees observed multicultural counselling competence due to its excellent reliability and validity.